Concomitant quantification of targeted drug delivery and biological response in individual cells - Pinto, Massimo (BioTechniques, 2007)
Targeted therapies result in heterogeneous drug delivery, often with highly variable drug uptake in the targeted cells and significant numbers of cells that are essentially untargeted. However both the variably targeted cells and neighboring bystander cells may respond to the treatment. Using ionizing radiation as an example of a targeted therapeutic agent, we describe a quantitative immunofluorescence-based approach for concomitant quantification of exposure and measurement of biological responses in both targeted and bystander cells. Cultures of human skin fibroblasts are co-pulse-labeled with 3H-deoxycytidine (3H-dC) and bromodeoxyuridine (BrdU). The labeled cells, identified by BrdU immunofluorescence, are internally irradiated by low-energy beta-particles emitted by incorporated 3H-dC. BrdU immunofluorescence intensity is proportional to radioactivity incorporated and, therefore, to radiation dose rate. Cell-cycle arrest in G2 is measured in labeled cells as function of dose rate. Stress responses in bystander cells, indicated by a G1 checkpoint, are concomitantly measured with a flow cytometric-cumulative labeling index (FCM-CLI) assay. The overall approach presented herein may be useful in the context of evaluating responses to targeted drug delivery